Eliminating breast surgery for invasive breast cancer in exceptional responders to neoadjuvant systemic therapy: a multicentre, single-arm, phase 2 trial. Issue 12 (December 2022) - Kuerer, Henry M; Smith, Benjamin D; Krishnamurthy, Savitri; Yang, Wei T; Valero, Vicente; Shen, Yu; Lin, Heather; Lucci, Anthony; Boughey, Judy C; White, Richard L; Diego, Emilia J; Rauch, Gaiane M; et al.
Summary: Background: Neoadjuvant systemic therapy (NST) for triple-negative breast cancer and HER2-positive breast cancer yields a pathological complete response in approximately 60% of patients. A pathological complete response to NST predicts an excellent prognosis and can be accurately determined by percutaneous image-guided vacuum-assisted core biopsy (VACB). We evaluated radiotherapy alone, without breast surgery, in patients with early-stage triple-negative breast cancer or HER2-positive breast cancer treated with NST who had an image-guided VACB-determined pathological complete response. Methods: This multicentre, single-arm, phase 2 trial was done in seven centres in the USA. Women aged 40 years or older who were not pregnant with unicentric cT1–2N0–1M0 triple-negative breast cancer or HER2-positive breast cancer and a residual breast lesion less than 2 cm on imaging after clinically standard NST were eligible for inclusion. Patients had one biopsy (minimum of 12 cores) obtained by 9G image-guided VACB of the tumour bed. If no invasive or in-situ disease was identified, breast surgery was omitted, and patients underwent standard whole-breast radiotherapy (40 Gy in 15 fractions or 50 Gy in 25 fractions) plus a boost (14 Gy in seven fractions). The primary outcome was the biopsy-confirmed ipsilateral breast tumour recurrence rate determined using the Kaplan-Meier method assessed in the per-protocol population. Safety was assessed in all patients who received VACB. This study has completed accrual and is registered with ClinicalTrials.gov, NCT02945579 . Findings: Between March 6, 2017, and Nov 9, 2021, 58 patients consented to participate; however, four (7%) did not meet final inclusion criteria and four (7%) withdrew consent. 50 patients were enrolled and underwent VACB following NST. The median age of the enrolled patients was 62 years (IQR 55–77); 21 (42%) patients had triple-negative breast cancer and 29 (58%) had HER2-positive breast cancer. VACB identified a pathological complete response in 31 patients (62% [95% CI 47·2–75·4). At a median follow-up of 26·4 months (IQR 15·2–39·6), no ipsilateral breast tumour recurrences occurred in these 31 patients. No serious biopsy-related adverse events or treatment-related deaths occurred. Interpretation: Eliminating breast surgery in highly selected patients with an image-guided VACB-determined pathological complete response following NST is feasible with promising early results; however, additional prospective clinical trials evaluating this approach are needed. Funding: US National Cancer Institute (National Institutes of Health).